Simulation and Economic Analysis of Parabolic Trough Solar Assisted Single Effect Absorption Chiller for Famagusta, Cyprus - Sahebari, Reyhaneh Jabbari (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This research contemplates on the valuable utilization of solar based energy intended for a restricted region in the Mediterranean basin. Especially in Mediterranean section with high solar gains and high cooling demands, solar cooling will become more and more an alternative to established cooling systems. Solar energy turns out to be progressively well-known and the accessible solar oriented market is explored with the point of selecting and evaluating a pilot locale for a promising solar based application. The system is displayed and assessed in details for the authentic related analysis application. The goal of this study is to access the traces of using underground water temperature instead of the inlet temperature of condenser on the energy outputs of the generator, the condenser and the evaporator, moreover, to investigate the feasibility of a solar single lithium bromide-water absorption cooling system for Famagusta, Cyprus. The system has been intended to supply cooling loads of the office building area of approximately 200 m² for working hours from 9 am to 16 pm, 5 days a week, in all hot weather states of Famagusta. TRNSYS software program has been used to estimate the performance of the system throughout the summer season. The performance calculations indicate that:  A 35kW absorption chiller is sufficient to appropriate the 200 m2 office space cooling requirements,  Use of 30 m2 parabolic trough collectors will be sufficient to operate the absorption chiller,  22℃ underground water is better to use in condenser and absorber instead of cooling tower water, which is commonly used in industries that provides a minimum sink temperature of 32℃,  COP of the system is obtained as 0.672 for 22℃ of the condenser inlet temperature of underground water. Keywords: solar absorption cooling system, parabolic trough solar collector, Cyprus climate conditions, life cycle cost analysis

ÖZ: Bu araştırma, Akdeniz havzasındaki sınırlı bir bölgeye yönelik güneş enerjisine dayalı enerjinin değerli kullanımı üzerinde düşünülmektedir. Özellikle Akdeniz bölümünde yüksek güneş enerjisi kazanımı ve yüksek soğutma ihtiyacı ile güneş soğutması, kurulan soğutma sistemlerine göre daha fazla seçilen seçenek olacaktır. Güneş enerjisi (solar enerji) aşamalı olarak uygulanarak bilinir ve erişilebilir olan güneş odaklı uygulama pazarı, umut verici bir şekilde güneş temelli uygulama için bir pilot yerleşim seçimi ve değerlendirmesi noktasında kurularak araştırılır. Sistem, gerçek ve güvenilirlikle ilgili analiz uygulaması için ayrıntılı olarak görüntülenir ve değerlendirilir. Bu yazının amacı, jeneratörün enerji çıkışlarındaki yoğunlaşmanın giriş sıcaklığı yerine yeraltı suyu sıcaklığı kullanma izlerini tahmin etmektir. Kondansatör ve buharlaştırıcı, Gazimağusa Kıbrıs için güneşi kullanarak tekli lityum bromür su soğurma ve soğutma sisteminin fizibilitesini sürükleyecektir (sürdürülebilecektir). Sistem, çalışma saatleri için sabah 09: 00'dan 16: 00'a kadar yaklaşık 200 m² ‘lik bir ofis binası alanının soğutma yüklerini tedarik etmeyi amaçlamıştır. Sistem modeli parabolik Geçiş (sürgü) toplayıcıları; sıcak bir depoda, bir LiBr-water ‘lik emici soğutucu ve fan soğutucu entegre sayılarını hariç tutmuştur. Performans ve maliyet üzerindeki etkiler gözden geçirilmiştir. Performans hesaplamaları sonucu şu bulgulara varılıyor:  35kW emici bir soğutucu, 200 m² ofis alanı soğutma gereksinimlerini karşılamak için yeterlidir.  Soğutucunun çalışmasını isteyen 30 m² 'lik toplayıcılardır.  22 ℃‘deki yer altı suyu, yoğunlaştırıcı ve soğurucuda çalişmasi için soğutma kulesi yerine ki minimum su sıcaklığı yaklaşık 32 ℃’dir, daha iyi kullanılır.  Kondansatör giriş soğutma suyu sıcaklığı 22 ° C için, soğutma çevriminin etkinlik kat sayısı (COP) 0.672 elde edilmiştir. Anahtar kelimeler: güneş enerjisi soğutma sistemi, parabolik oluk tipi güneş kolektörü, Kıbrıs iklim koşulları, yaşam döngüsü maliyet analizi
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2017. Supervisor: Prof. Dr. Uğur Atikol.
Keywords: Mechanical Engineering; Solar energy-Solar air conditioning-Solar Cooling-Cyprus; Solar thermal energy; solar absorption cooling system; parabolic trough solar collector; Cyprus climate conditions; life cycle cost analysis